Antioxidant activity of Cissampelos pareira on benzo(a)pyrene-induced mucosal injury in mice - Amresh G.; Rao C.V.; Singh P.N. (My University, 2025)
This study evaluated the antioxidant activity of Cissampelos pareira (L.) Hirsuta (family: Menispermaceae). The roots of the C pareira (50% ethanol extract) were found to contain a large amount of polyphenols and exhibit significant and dose-dependent reducing ability, indicative of potent antioxidant ability both in vitro and in vivo. The C pareira extract (CPE) showed significant antioxidant activity in the 1,1-diphenyl-2-picrylhydrazyl assay. The ability of CPE to scavenge reactive oxygen and nitrogen species was tested; and it was found to significantly scavenge superoxide, hydrogen peroxide, hydroxyl radicals, and nitric oxide at a dose regimen of 50 to 400 μg/kg in vitro. The CPE also inhibited hydroxyl radical-induced oxidation of proteins in vitro. The efficacy of CPE was further tested in vivo. It was found to exhibit a potent protective activity in an acute oxidative tissue injury animal model: benzo(a)pyrene-induced gastric toxicity in mice. Treatment with CPE at a dose regimen of 50 and 100 mg/kg body weight in mice, significantly and dose dependently protected the gastric mucosa against benzo(a)pyrene-induced oxidative stress. The CPE, significantly and dose-dependently, also afforded protection against gastric lipid peroxidation, glutathione levels, and activities of other antioxidant enzymes, namely, superoxide dismutase, catalase, glutathione peroxidase, and glutathione S-transferase. These results indicate the compelling antioxidant activity of C pareira in vitro and against the stress induced by the gastric carcinogen benzo(a)pyrene in vivo. This is the first report on the antioxidant properties of C pareira against benzo(a)pyrene. © 2007 Elsevier Inc. All rights reserved.